A prospective longitudinal in vivo 1H MR spectroscopy study of the SIV/macaque model of neuroAIDS - Halpern Elkan; Masliah Eliezer; Sehgal Prabhat K; He Julian; Lentz Margaret R; Kim John P; Greco Jane B; Ratai Eva; Westmoreland Susan V; Fuller Robert A; Lackner Andrew A; González R Gilberto (BMC Neuroscience, 2004)
Abstract Background The neurological complications of HIV infection remain poorly understood. Clinically, in vivo 1H magnetic resonance spectroscopy (MRS) demonstrates brain injury caused by HIV infection even when the MRI is normal. Our goal was to undertsand the dynamics of cerebral injury by performing a longitudinal in vivo 1H MRS study of the SIV/macaque model of neuroAIDS. Results Eight rhesus macaques were infected with SIVmac251 and serially imaged with MRI and 1H MRS to terminal AIDS or the endpoint of 2 years. During acute infection, there were stereotypical brain MRS changes, dominated by a significant elevation of the Cho/Cr ratio in the frontal cortex. Subsequently, brain metabolic patterns diverged between animals. There was an elevation of basal ganglia Cho/Cr four weeks post-inoculation in 2 animals that developed SIV encephalitis (p = 0.022). Metabolite ratios averaged across all 8 animals were not significantly different from baseline at any time point after 2 weeks post inoculation. However, linear regression analysis on all 8 animals revealed a positive correlation between a change in frontal lobe Cho/Cr and plasma viral load (P < 0.001, R = 0.80), and a negative correlation between NAA/Cr in the basal ganglia and the plasma viral load (P < 0.02, R = -0.73). No MRI abnormalities were detected at any time. Conclusions After infection with SIV, macaque brain metabolism changes in a complex manner that is dependent on brain region, host factors and viral load. An elevation of basal ganglia Cho/Cr 4 weeks after SIV infection may be marker of a propensity to develop SIV encephalitis. Elevations of Cho/Cr, often observed in CNS inflammation, were associated with increased plasma viral load during acute and chronic infection. Evidence of neuronal injury in the basal ganglia was associated with increased plasma viral load in the chronic stage of infection. These observations support the use of drugs capable of controlling the viral replication and trafficking of virus into the CNS, and may help explain the reduction in incidence of HIV-associated dementia in the era of HAART despite the inability of most of those drugs to effectively enter the CNS.